244 A Systematic Review of Epileptiform Changes During Sevoflurane Anesthesia In Infants and Children. (April 2022) - Gizzo, Luciana; Ivenitsky, Daria; Ferrera, Alexander; Tam, Matthew; Legatt, Alan D.; Yozawitz, Elissa G.; Lo, Yungtai; Li, Guohua; Shinnar, Shlomo; Chao, Jerry
Abstract : OBJECTIVES/GOALS: Early clinical case reports have described incidental epileptiform changes during electrophysiological monitoring. The objective of this study was to perform a systematic review of all existing investigations of epileptiform activity during sevoflurane use in pediatric anesthesia. The heterogenous EEG data will be analyzed in a meta analysis METHODS/STUDY POPULATION: A targeted, PICO-based clinical question was crafted and registered a priori on PROSPERO on 3/19/21. Under the guidance of a librarian from the Albert Einstein College of Medicine, a boolean search string was generated to search articles and gray literature for terms such as pediatric, sevoflurane and electroencephalogram in PubMed, OVID, Cochrane, Google Scholar, etc. We utilized the software platform tool COVIDENCE to manage our review. 495 references were imported for initial screening. 56 English-language, full-text studies were included for further review. The final 13 references were included in data extraction and Newcastle-Ottawa bias assessment. The characteristics of the studies and their primary outcomes were collected in tabular form. Strategies for data synthesis were discussed weekly. RESULTS/ANTICIPATED RESULTS: Epileptiform changes reported in the literature during pediatric sevoflurane anesthesia ranged from 0 - 95%. EEG data were acquired using a variety of recording systems with variable number of leads and heterogeneous outcomes reported. The periods of anesthesia monitoring were also heterogeneous. Characteristics of the studies are presented in Table 1. 495 references were imported for screening with 13 final references for data extraction. EEG abnormalities were reported in 204/649 (31.4%) subjects ranging in age from neonate to 18 years; the majority of studies utilized less than 16 channels of (10/13, 76.9%) (Table 1). There was variability in sevoflurane dosing, premedication (e.g., midzolam, hydroxyzine), and periods of anesthesia monitored. DISCUSSION/SIGNIFICANCE: There was heterogeneity noted across reviewed literature including study design, phases of anesthesia, ventilation methods, number of EEG leads recorded and adjuvant anesthetics administered. Nevertheless, this review rigorously classified epileptiform activity during Sevoflurane thereby influencing modern anesthesia.